Review on Impact of Eucalyptus Plantation on the Soil - Amenu, Bekele Tona (International Journal of Scientific Research in Civil Engineering, 2017)
This paper takes up a number of issues with the planting eucalyptus trees impacts of on the environment in general and soil in particular. Explains that diversity of eucalyptus, eucalyptus and soil erosion soil nutrient and eucalyptus. Eucalyptus and water cycle, interaction of eucalyptus with other plants and animals allelopathy effect of eucalyptus and to identify the impacts of eucalyptus on crops. Soil nutrients and soil water. It further noted that, eucalyptus species have effects on the germination, radical and growth of a given crop. This adverse effect is motivated by proper management of eucalyptus plantation. Studying the impacts of eucalyptus plantation on the environment is to determine the adverse effect and the use of planting eucalyptus on the ecology of Ethiopia. Many ideas are raised on planting eucalyptus that is planting eucalyptus has arguments for and against because of their adverse effect and use they give for the environment.
Keywords: Soil; Eucalyptus; Allelopathy; Erosion